Effects of mianserin, a new antidepressant, on the in vitro and in vivo uptake of monoamines. - Goodlet, I (1977)
1 The effects of mianserin and of selected tricyclic antidepressants were compared in a number of monoamine uptake models. 2 The ability of mianserin to block the noradrenergic neurone membrane amine pump of rabbit brain stem slices was comparable to that of imipramine and amitriptyline and less than that of desipramine and nortriptyline. Both mianserin and desipramine were competitive inhibitors of noradrenaline uptake in vitro. The effect of mianserin on noradrenaline uptake in vivo was studied both peripherally and centrally. The ability of 6-hydroxydopamine to lower rat heart noradrenaline levels was found to be very sensitive to inhibition by tricyclic antidepressants. Mianserin was active in this model. However, its ability to block the 6-hydroxydopamine-induced fall in rat heart noradrenaline concentration was appreciably less than that of the tricyclics studied. 3 Mianserin, like tricyclic antidepressants, was essentially devoid of effect on dopamine uptake both in vitro and in vivo. 4 The ability of mianserin to inhibit [3H]-5-hydroxytryptamine uptake by rat hypothalamic synaptosomes was appreciably less than that of the tricyclic antidepressants studied. Mianserin was essentially devoid of effect on rat brain 5-hydroxytryptamine uptake in vivo. 5 It is concluded that in certain situations large doses of mianserin may block noradrenaline uptake in vivo. However, in no way does mianserin rival tricyclic antidepressants in blocking monoamine uptake in vivo. The clinical efficacy of mianserin cannot be attributed to inhibition of monoamine uptake.